La presencia de monticulos tipo Mima en la Argentina en relación con roedores del género Ctenomys - Roig, V. G.; Cox, G. W. (Ecosur, 2023)
The discovery of Mima mounds pocking the Pampean region in the south-east of San Luis, south of Córdoba and north of La Pampa, as well as in some Monte regions in Mendoza, confirms the hypothesis that fossorial rodents are the origin of this type of phenomenon and that such mounds are present in different regions of the world coinciding with the presence of families of fossorial rodents showing similar morphology and behavior. This similarity with geomyds of the United States and other families from West and South Africa, becomes evident in Argentine Ctenomydae, which activity is responsible for the formation of this type of relief, Which has nowadays disappeared in most of the central part of the country due to agricultural practices. The discovery of Mima mounds in Argentina unquestionably confirms the discussed origin of this type of topographic accident, which has been subject to the most varied interpretations.